Relationships among traits of tropical early maize cultivars in contrasting environments - Badu-Apraku, Baffour; Akinwale, R.O.; Ajala, S.O.; Menkir, A.; Fakorede, M.A.B.; Oyekunle, M. (Wiley, 2011)
Secondary traits can improve precision with which drought or low soil nitrogen (low-N) tolerant maize (Zea mays L.) genotypes are identified, compared to measuring only grain yield under each stress. The objective of this study was to identify secondary traits for indirect selection for yield improvement under drought and/or low-N. Two sets of experiments were conducted at four locations in Nigeria for 2 yr. In the first experiment, cultivars were evaluated under low (30 kg ha−1) and high (90 kg ha−1) N and drought and well-watered environments in the second experiment. Most reliable traits for selection for yield under drought were ear aspect (EASP), plant aspect (PASP), anthesis-silking interval (ASI), and number of ears per plant (EPP). Days to anthesis (DYA) and silking (DYS) were the most reliable under well-watered environments. Under low-N, most reliable traits were DYA, DYS, stay green characteristic (LDTH), ASI, plant height (PLHT), EPP, EASP, and PASP whereas PLHT, EPP, PASP, and EASP were most reliable traits under high-N environments. The ASI, EPP, EASP, and PASP were identified as most reliable traits for simultaneous selection of drought and low-N tolerant genotypes. Under drought, cultivars TZE-Y DT STR C4, TZE-W DT STR C4, and TZE Comp 3 DT C1F2 were outstanding and closest to the ideal cultivar. Seven cultivars were closest to the ideal under low-N, two of which were among the three selected under drought stress. Faster progress in selecting for improved grain yield is possible using EPP, EASP, PASP, and ASI under either drought or low-N.